The PAI Teacher's Strategy In Developing Student Achievement And Talents At SMP Muhammadiyah 7 Medan - Riski Panjaitan (Yayasan Rahmat Islamiyah, 2024)
This study aims to explore the strategies employed by Islamic Religious Education (PAI) teachers in developing students' achievements and talents at SMP Muhammadiyah 07 Medan. The research method used is descriptive qualitative, with data collected through interviews, observation, and documentation. The results show that PAI teachers implement various effective strategies, such as project-based learning, problem-based learning, and differentiated approaches tailored to the needs of the students. Additionally, religious extracurricular activities play a crucial role in helping students express their talents beyond the formal academic context. Overall, the strategies applied by PAI teachers have successfully developed both academic and non-academic student achievements and talents. This research highlights the importance of innovative, collaborative, and technology-based approaches in maximizing student potential, offering significant implications for improving PAI learning in schools.